How Physics Teachers’ Pedagogical Content Knowledge is Captured: A Literature Review - Wulandari, Ika Pratiwi; Purwaningsih, Endang; Munfaridah, Nuril (Kasuari: Physics Education Journal (KPEJ), 2024)
We conducted a systematic literature review to find out how physics teachers’ PCK has been captured over the 10 years. Following  identification and screening process using PRISMA flowchart method, we found 29 articles and conference proceedings are eligible. Three instruments often used by researchers to capture physics teachers' PCK are interview guidelines, CoRes and questionnaires. We explore the impact of physics teachers' PCK influences physics learning for students, we need to see teachers' enacted PCK in the classroom, observation sheet or learning video assessment sheet is required. Among factors that affect physics teachers' PCK is teacher development program. Things that should be considered in teacher's PCK development program are phases when teachers develop lesson plans (development phase) and phases when teachers perform the lessons (class enactment phase). The connection between capture physics teachers' PCK, correlation between physics teachers' PCK on students' learning, and physics teachers' PCK development program were discussed.